A phosphorus-free surface pretreatment agent for improving the adhesion of low-temperature curing electrophoretic paint
By using phosphorus-free surface pretreatment agent, chemical cross-linking and catalytic effects of components such as fluorozirconic acid, zirconium nitrate, blocked isocyanate modified silica sol and tin compounds, the problems of adhesion and roughness of low-temperature curing electrophoretic paint are solved, and adhesion and appearance properties similar to high-temperature curing are achieved.
Patent Information
- Application Number
- CN202411935958.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
During the curing process of low-temperature curing electrophoretic paint, the degree of chemical crosslinking between the zirconium-based film and the electrophoretic paint is reduced, resulting in a decrease in adhesion and the appearance roughness of the paint film.
Phosphorus-free surface pretreatment agent is used, which contains fluorozirconic acid solution, zirconium nitrate pentahydrate, blocked isocyanate modified silica sol solution, tin nitrate and polyether compounds. Through the chemical cross-linking and catalytic action of these components, the interface binding force between the zirconium-based film and the electrophoretic paint film is enhanced.
It effectively improves the adhesion of the low-temperature cured electrophoretic paint film, so that it is not weaker than the high-temperature cured electrophoretic paint film, and at the same time reduces the roughness of the paint film, achieving similar performance to high-temperature curing.
Smart Images

Figure BDA0005211515900000011 
Figure BDA0005211515900000021 
Figure BDA0005211515900000022
Abstract
Description
Technical Field
[0001] The invention relates to a phosphorus-free surface pretreatment agent for improving the adhesion of low-temperature curing electrophoretic paint. Background Art
[0002] Low-temperature curing electrophoretic paint is a product that achieves a lower curing temperature by using a low-temperature deblocking curing agent. In order to match the leveling properties of electrophoretic paint during low-temperature curing, the existing technology designs the polymer segment structure of the electrophoretic paint resin to reduce the viscosity flow temperature T f , thereby obtaining a good paint film appearance and reducing the roughness of the paint film. Phosphorus-free pretreatment technology is used to provide a hydroxyl-rich surface for the metal surface. The high-temperature curing process of the electrophoretic paint can provide sufficient energy for the chemical cross-linking of the zirconium-based film and the electrophoretic paint, thereby ensuring excellent adhesion between the electrophoretic paint and the zirconium-based film. As the curing temperature of the low-temperature curing electrophoretic paint decreases, the degree of chemical cross-linking between the zirconium-based film and the electrophoretic paint will be greatly reduced compared to high-temperature curing, which will have a negative impact on the roughness and adhesion of the electrophoretic paint film. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a phosphorus-free surface pretreatment agent for improving the adhesion of low-temperature curing electrophoretic paint. The phosphorus-free surface pretreatment agent can effectively enhance the interfacial bonding force between the zirconium-based film and the electrophoretic paint film, so that the electrophoretic paint film exhibits an adhesion that is not weaker than that of the high-temperature curing electrophoretic paint film.
[0004] Technical solution: The phosphorus-free surface pretreatment agent of the present invention contains the following components by mass per liter of pretreatment agent: 75-100g of fluorozirconic acid solution, 10-15g of zirconium nitrate pentahydrate, 100-150g of blocked isocyanate-modified silica sol solution, 4-5g of nitric acid solution, 10-15g of tin nitrate, 10-15g of polyether compound and the balance is water.
[0005] Wherein, the mass concentration of the fluorozirconic acid (water) solution is 45-50%.
[0006] The blocked isocyanate-modified silica sol solution is prepared by the following method, which specifically comprises the following steps:
[0007] (1) dissolving 3-isocyanate propyl trimethoxy silane in an organic solvent, adding a solution containing a blocking agent 3,5-dimethylpyrazole dropwise thereto under the protection of an inert gas, reacting at a high temperature, and removing the organic solvent after the reaction to obtain blocked isocyanate propyl trimethoxy silane; isocyanate is very active in an aqueous solution, so it needs to be blocked first so that it can be stably present at room temperature;
[0008]
[0009] (2) dissolving blocked isocyanate propyltrimethoxysilane in anhydrous ethanol to obtain a modifier solution; slowly dropping the modifier solution into the silica sol solution, reacting at room temperature after the dropping is completed, and obtaining a blocked isocyanate-modified silica sol solution after the reaction.
[0010]
[0011] Wherein, in step (1), the molar ratio of 3-isocyanatepropyltrimethoxysilane to the blocking agent 3,5-dimethylpyrazole is 1:1.
[0012] Wherein, in step (1), the reaction temperature is 70-75°C and the reaction time is 5.5-6h.
[0013] Wherein, in step (2), the silica sol solution is prepared by the following method, specifically: dissolving tetraethyl orthosilicate (TEOS) in anhydrous ethanol to obtain a TEOS solution; mixing anhydrous ethanol, high-purity water and ammonia water (mass fraction of 25%) to obtain a mixed solution; slowly dropping the TEOS solution into the above mixed solution, and reacting at room temperature after the dropping is completed to obtain a silica sol solution.
[0014] Among them, in the mixed liquid, the mixing volume ratio of anhydrous ethanol, high-purity water and ammonia water is 80:2:1~1.5.
[0015] The mass volume ratio of blocked isocyanate propyltrimethoxysilane to tetraethyl orthosilicate is 1 g:5-10 mL.
[0016] Wherein, in step (2), the solid content of the blocked isocyanate-modified silica sol solution is not higher than 10%; this solid content can improve the stability of the system.
[0017] Wherein, the structural formula of the polyether compound is:
[0018]
[0019] The polyether compound of the structure of the present invention is reported in the document “Zu Xihong, Hu Jianqing, Tu Weiping. Research progress of new cathode electrophoretic coatings [J]. Electroplating and Finishing, 2008, 27(8): 51-54.”
[0020] The mechanism of action of the phosphorus-free surface pretreatment agent of the present invention is as follows: the blocked isocyanate modified silica sol solution synthesized by the present invention contains blocked isocyanate groups on its surface which can be unblocked at low temperature (can be unblocked at about 120°C). The low-temperature curing process can unblock the blocked isocyanate groups to generate active isocyanate groups. The active isocyanate groups can react with active groups (hydroxyl groups, amino groups, etc.) in the paint film to generate covalent bonds, thereby greatly improving the degree of chemical crosslinking between the zirconium-based film and the electrophoretic paint film, and further improving the interfacial bonding strength between the zirconium-based film and the electrophoretic paint film. In addition, the zirconium-based film layer formed by the pretreatment agent of the present invention is an organic / inorganic hybrid amorphous zirconium hydroxide. After the tin compound is doped in the film, it has a catalytic effect on the low-temperature curing process of the electrophoretic paint film (the tin compound can coordinate with the -NCO group of the isocyanate, polarize the -NCO, and make the positively charged carbon atoms in the isocyanate molecule more active, thereby improving its reaction activity and making it easier to react with the active groups (hydroxyl, amino, etc.) in the paint film to form covalent bonds); at the same time, the introduced polyether compound can be adsorbed on the surface of the zirconium-based film, and can diffuse into the electrophoretic paint film during the electrophoretic curing process, thereby improving the leveling of the electrophoretic paint film, ensuring that the electrophoretic paint film has good leveling, while reducing the roughness of the paint film and synergistically improving the adhesion, so that its adhesion and roughness are basically equivalent to those of the high-temperature cured electrophoretic paint film.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the phosphorus-free surface pretreatment agent of the present invention can enhance the surface functionalization of the zirconium-based film, so that its surface has a large number of hydroxyl groups and also has blocked isocyanate groups that can be unblocked at low temperature. By utilizing the chemical cross-linking reaction of isocyanate groups and the catalytic effect of tin compounds, the number of covalent bonds between the zirconium-based film layer and the electrophoretic paint film can be effectively increased (i.e., the degree of chemical cross-linking between the zirconium-based film and the electrophoretic paint film during the low-temperature curing process is increased), thereby increasing the interfacial bonding force between the zirconium-based film and the electrophoretic paint film during the low-temperature curing process, and ensuring that the low-temperature cured electrophoretic paint film has good adhesion; at the same time, the polyether compounds adsorbed on the surface of the zirconium-based film can diffuse into the electrophoretic paint film to improve the leveling of the electrophoretic paint film, thereby reducing the roughness of the electrophoretic paint film. DETAILED DESCRIPTION
[0022] Example 1
[0023] The phosphorus-free surface pretreatment agent of the present invention is prepared as follows: per liter of the phosphorus-free surface pretreatment agent, the following components are contained in weight: 75 g of fluorozirconic acid solution (50 wt.%); 15 g of zirconium nitrate pentahydrate; 10 g of tin nitrate; 4 g of nitric acid solution (mass fraction is 68%); 100 g of blocked isocyanate-modified silica sol solution; 15 g of polyether compound; and the balance is deionized water.
[0024] The blocked isocyanate-modified silica sol solution is prepared by the following method, which specifically comprises the following steps:
[0025] (1) dissolving 2.05 g of 3-isocyanate propyl trimethoxy silane in 50 mL of acetone to obtain solution A; dissolving 0.96 g of 3,5-dimethylpyrazole (DMP) in 10 mL of acetone to obtain solution B; slowly dropping solution B into solution A under nitrogen protection, and after the dropping is completed, reflux at 70° C. for 6 h; after the reaction is completed, the acetone solvent is removed by rotary evaporation at 40° C. to obtain blocked isocyanate propyl trimethoxy silane;
[0026] (2) Dissolve 2.5 mL of tetraethyl orthosilicate (TEOS) in 20 mL of anhydrous ethanol to obtain a TEOS solution; add 80 mL of anhydrous ethanol, 2 mL of high-purity water and 1 mL of ammonia water (mass fraction of 25%) into a reaction container in turn and mix to obtain a mixed solution; start stirring and slowly drop the TEOS solution into the mixed solution, and react at room temperature for 12 hours after the addition is complete to obtain a silica sol solution; dissolve 0.5 g of blocked isocyanate propyltrimethoxysilane in 20 mL of anhydrous ethanol to obtain a modifier solution; slowly drop the modifier solution into the silica sol solution, and react at room temperature for 12 hours after the addition is complete, add the reaction product into a dialysis bag, dialyze for 7 days, and adjust the solid content of the dialyzed product to 10 wt.%, to obtain a blocked isocyanate-modified silica sol solution.
[0027] Among them, the structural formula of the polyether compound is:
[0028] The use concentration of the phosphorus-free surface pretreatment agent of the present invention is 5‰, that is, 5g of the phosphorus-free surface pretreatment agent of Example 1 is added to deionized water to prepare a working solution with a mass concentration of 5‰, and the working solution is adjusted to pH = 4.5 with sodium hydroxide solution and ammonium bifluoride solution, and free fluorine = 60ppm.
[0029] The phosphorus-free surface pretreatment agent of Example 1 is applied:
[0030] Test plate: Use commercially available standard cold-rolled iron plate with specifications of (150mm×70mm×0.8mm).
[0031] Process flow: degreasing and oil removal → tap water washing → pure water washing → phosphorus-free surface pretreatment → tap water washing → pure water washing → electrophoretic coating → curing
[0032] Brief introduction of each process:
[0033] Degreasing treatment: Use a commercially available heated cold-rolled plate degreasing agent to soak the cold-rolled plate at 50°C for 5 minutes, supplemented by manual swinging and scrubbing to ensure the surface is degreased and clean.
[0034] Washing after degreasing: Wash in tap water at room temperature for 1 minute, or in pure water for 1 minute.
[0035] Phosphorus-free surface pretreatment: Use the working solution of Example 1 to soak the cold-rolled plate at room temperature for 3 minutes, then wash it and perform electrophoretic coating and curing.
[0036] Electrophoretic coating: Low-temperature curing electrophoretic paint Powercron 6700 water-based cathode electrophoretic coating produced by PPG on the market, with a film thickness of 20-22μm. The washed electrophoretic cold-rolled sheet was cured at 150℃ for 20 minutes, and then placed at room temperature for 24 hours.
[0037] Example 2
[0038] The preparation of the phosphorus-free surface pretreatment agent of the present invention: each liter of the phosphorus-free surface pretreatment agent contains the following components by mass: 100 g of fluorozirconic acid solution (50 wt.%); 10 g of zirconium nitrate pentahydrate; 15 g of tin nitrate; 5 g of nitric acid solution (mass fraction 68%); 150 g of blocked isocyanate-modified silica sol solution; 10 g of polyether compound; the balance is deionized water. In Example 2, the preparation of the blocked isocyanate-modified silica sol solution is the same as in Example 1, and the structural formula of the polyether compound is:
[0039]
[0040] Comparative Example 3
[0041] A preparation of a phosphorus-free surface pretreatment agent: per liter of the phosphorus-free surface pretreatment agent, the following components are contained by mass: 75 g of fluorozirconic acid solution (50 wt.%); 15 g of zirconium nitrate pentahydrate; 10 g of tin nitrate; 4 g of nitric acid solution (mass fraction 68%); 100 g of blocked isocyanate-modified silica sol solution; the balance is deionized water. In Comparative Example 1, the preparation of the blocked isocyanate-modified silica sol solution is the same as that of Example 1.
[0042] Comparative Example 4
[0043] A preparation of a phosphorus-free surface pretreatment agent: each liter of the phosphorus-free surface pretreatment agent contains the following components by mass: 75 g of fluorozirconic acid solution (50 wt.%); 15 g of zirconium nitrate pentahydrate; 4 g of nitric acid solution (mass fraction 68%); 100 g of blocked isocyanate-modified silica sol solution; 15 g of polyether compound; the balance is deionized water. In comparative example 2, the preparation of the blocked isocyanate-modified silica sol solution is the same as that of example 1, and the structure of the polyether compound is also the same as that of example 1.
[0044] Comparative Example 5
[0045] A preparation of a phosphorus-free surface pretreatment agent: Each liter of the phosphorus-free surface pretreatment agent contains the following components by mass: 75 g of fluorozirconic acid solution (50 wt.%); 15 g of zirconium nitrate pentahydrate; 10 g of tin nitrate; 4 g of nitric acid solution (mass fraction 68%); 100 g of blocked isocyanate-modified silica sol solution; 15 g of polyether compound; the remainder is deionized water. In comparative example 3, the preparation of the blocked isocyanate-modified silica sol solution is the same as that of example 1, and the structure of the polyether compound is different from that of example 1, wherein the structural formula of the polyether compound is: The polyether compound of this structure comes from the literature "Zu Xihong, Hu Jianqing, Tu Weiping. Research progress of new cathode electrophoretic coatings [J]. Electroplating and Finishing, 2008, 27(8): 51-54."
[0046] The pretreatment agents of Examples 1 to 2 and Comparative Examples 1 to 5 were all formulated into working solutions with a mass concentration of 5‰, and the cold-rolled iron plates were treated in the same manner as in Example 1; wherein the pretreatment agent used in Comparative Example 1 was a conventional silane film surface pretreatment agent in the prior art, and Comparative Example 2 was a high-temperature (180°C) cured electrophoretic paint coating cured sample after treatment with the phosphorus-free surface treatment agent of Example 1.
[0047] The general properties of the paint films obtained in Examples 1 to 2 and Comparative Examples 1 to 5 are shown in Table 1.
[0048] Table 1
[0049]
[0050] The cold-rolled sheet treated with the phosphorus-free surface treatment agent of the present invention has excellent adhesion to the paint film, and both the cross-cut test and the impact resistance test are qualified. The two test methods cannot identify the adhesion difference of the products, and a cross-cut + impact resistance combined test method is required to be used for testing, and image recognition software is used to calculate the residual paint ratio.
[0051] Adhesion test and paint film roughness data are shown in Table 2
[0052] Table 2
[0053]
[0054] It can be seen from Table 2 that the cold-rolled iron plate treated with the phosphorus-free surface pretreatment agent of the present invention and the low-temperature (150°C) curing electrophoretic paint coating curing sample has obvious adhesion advantages and paint film roughness advantages over the test plate treated with the conventional silane film surface pretreatment agent, and can achieve adhesion and appearance performance similar to that of high-temperature curing electrophoretic paint. In addition, the polyether compound on the surface of the zirconium-based film layer can enhance the leveling of the paint film after electrophoretic coating, thereby reducing the roughness of the electrophoretic paint film; at the same time, the zirconium-based film layer is doped with tin compounds and blocked isocyanate modified silica sol, through the catalytic crosslinking of the tin compound and the chemical crosslinking of the blocked isocyanate in the zirconium-based film, and effectively improves the bonding force between the substrate and the electrophoretic paint film in the form of covalent bonds, thereby improving the salt spray performance and cyclic corrosion performance of the electrophoretic paint film.
Claims
1. A phosphorus-free surface pretreatment agent for improving the adhesion of low-temperature curing electrophoretic paint, characterized in that: Each liter of the pretreatment agent contains the following components by mass: 75-100g of fluorozirconic acid solution, 10-15g of zirconium nitrate pentahydrate, 100-150g of blocked isocyanate-modified silica sol solution, 4-5g of nitric acid solution, 10-15g of tin nitrate, 10-15g of polyether compound and the balance is water.
2. The phosphorus-free surface pretreatment agent according to claim 1, characterized in that: The mass concentration of the fluorozirconic acid solution is 45-50%.
3. The phosphorus-free surface pretreatment agent according to claim 1, characterized in that: The blocked isocyanate-modified silica sol solution is prepared by the following method, which specifically comprises the following steps: (1) dissolving 3-isocyanate propyl trimethoxy silane in an organic solvent, adding a solution containing a blocking agent 3,5-dimethylpyrazole dropwise thereto under the protection of an inert gas, reacting at a high temperature, and removing the organic solvent after the reaction to obtain blocked isocyanate propyl trimethoxy silane; (2) dissolving blocked isocyanate propyltrimethoxysilane in anhydrous ethanol to obtain a modifier solution; slowly dropping the modifier solution into the silica sol solution, reacting at room temperature after the dropping is completed, and obtaining a blocked isocyanate-modified silica sol solution after the reaction.
4. The phosphorus-free surface pretreatment agent according to claim 3, characterized in that: In step (1), 3-isocyanatepropyltrimethoxysilane and blocking agent 3,5-dimethylpyrazole are mixed in equimolar amounts.
5. The phosphorus-free surface pretreatment agent according to claim 3, characterized in that: In step (1), the reaction temperature is 70-75° C. and the reaction time is 5.5-6 h.
6. The phosphorus-free surface pretreatment agent according to claim 3, characterized in that: In step (2), the silica sol solution is prepared by the following method, specifically: dissolving tetraethyl orthosilicate in anhydrous ethanol to obtain a TEOS solution; mixing anhydrous ethanol, high-purity water and ammonia water to obtain a mixed solution; slowly adding the TEOS solution dropwise to the mixed solution, and reacting at room temperature after the addition is completed to obtain a silica sol solution.
7. The phosphorus-free surface pretreatment agent according to claim 6, characterized in that: In the mixed liquid, the mixing volume ratio of anhydrous ethanol, high-purity water and ammonia water is 80:2:1-1.
5.
8. The phosphorus-free surface pretreatment agent according to claim 6, characterized in that: The mass volume ratio of blocked isocyanate propyltrimethoxysilane to tetraethyl orthosilicate is 1 g:5-10 mL.
9. The phosphorus-free surface pretreatment agent according to claim 3, characterized in that: In step (2), the solid content of the blocked isocyanate-modified silica sol solution is not higher than 10%.
10. The phosphorus-free surface pretreatment agent according to claim 1, characterized in that: The structural formula of the polyether compound is: